La segmentación del consumidor en las comunidades virtuales de marca a través del coeficiente de adecuación: El caso empírico eDreams - Santos-Caballero, Adriana; Gil-Lafuente, Jaime (Rect@, 2016)
The increasing connectivity provided by the Internet and the increasing power of online consumers have turned the virtual brand communities into a relevant phenomenon, giving a better communication between businesses and consumers, these platforms often focus on mutual and specific interest (a brand, a product, etc.) and its members are usually united by a shared admiration for that interest. Where the contribution is the application of a new model of attitudinal loyalty going from the two references, classifying participants / customers according to their occupation. This will enable the brand to find new strategies according to customer segmentation / participants of the virtual brand community. It has been chosen to use the coefficient of Adequacy, because through it we can facilitate decision-making by obtaining data.